Optimizing the Expression of Polyethylene Terephtalate Hydrolase-Encoding Synthetic Gene in Escherichia coli Arctic Express (DE3) - Nataniel, Jocelyn; Ulfah, Maria; Achnafani, Dini; Nurhayati, Niknik; Sabbathini, Gabriela Christy; Wulandari, Sri Rezeki; Abinawanto, Abinawanto; Helianti, Is (Makara Journal of Science, 2024)
The waste of polyethylene terephthalate (PET) plastic waste in Indonesia is a pressing concern due to its slow degradation and potential environmental damage. One promising solution is to utilize polyethylene terephthalate hydrolase from Ideonella sakaiensis (IsPETase), an enzyme that specifically degrades PET. However, inducing the expression of IsPETase synthetic gene in Escherichia coli BL21 (DE3) has been challenging because much of it remains insoluble. This study aimed to express IsPETase in E. coli Arctic Express (DE3) and optimize the conditions to enhance its production. First, pET22b(+)pelB-IsPETase was inserted into E. coli Arctic Express (DE3). The recombinant E. coli Arctic Express (DE3) was induced with isopropyl-β-D-1-thiogalactopyranoside (IPTG) and incubated at 10 °C. The fraction expressing soluble IsPETase was determined in different culture media, IPTG concentrations, induction times, and soni-cation durations. Parameters were optimized using a one-factor-at-a-time approach and then evaluated based on esterase specific activity and SDS-PAGE analysis. Results showed that IsPETase can be expressed in extracellular, periplasmic, and cytoplasmic soluble fractions. However, the extracellular fraction should be concentrated. Subsequent optimization focused only on the cytoplasmic fraction under optimal conditions, achieving a threefold increase in PETase specific activity compared with that under uninduced IPTG conditions. The reaction of PETase enzyme with PET and PCL was proven by weight loss, Scanning electron microscope (SEM), and Fourier transform infrared spectroscopy (FTIR). Although successful IsPETase expression and production optimization have been achieved, the specific activity remains low, prompting the need for ongoing expression optimization.